Analysis Of Corporate Governance Mechanisms On Earnings Management In Indonesian Consumer Companies In 2018-2021 - Safira, Nina Dhani; Rahman, Aulia Fuad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The existence of information asymmetry and the tendency to achieve certain interests cause stakeholders to practice Earnings Management. This study aims to obtain empirical evidence regarding the effect of good corporate governance mechanisms represented by the audit committee, managerial ownership, and independent board of commissioners on earnings management practices. Earnings Management is measured using Discretionary Accruals using the performed-matched method developed by Kothari. The research sample consists of 47 consumption sub-sector companies or non-cyclical consumer companies on the Indonesia Stock Exchange (IDX) in 2018-2021. Hypothesis testing was carried out using multiple regression analysis. The results showed that the audit committee and independent board of commissioners had a negative effect on earnings management. Meanwhile, managerial ownership does not affect earnings management. Future researchers are expected to consider additional variables that have more influence on earnings management, extend the observation period, and use different measurement models. Abstrak Adanya asimetri informasi dan kecenderungan untuk meraih kepentingan tertentu menimbulkan para pemegang kepentingan melakukan praktik Earnings Management. Penelitian ini bertujuan untuk memperoleh bukti empiris mengenai pengaruh mekanisme good corporate governance yang diinterpresentasikan dengan komite audit, kepemilikan manajerial, dan dewan komisaris independen terhadap praktik earnings management. Earnings Management diukur dengan menggunakan Discretionary Accruals dengan metode performed-matched yang dikembangkan oleh Kothari. Sampel penelitian terdiri dari 47 perusahaan sub sektor konsumsi atau perusahaan consumer non-cyclical di Bursa Efek Indonesia (BEI) pada tahun 2018-2021. Pengujian hipotesis dilakukan menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa komite audit dan dewan komisaris independent berpengaruh negatif terhadap earnings management. Sementara, kepemilikan manajerial tidak berpengaruh terhadap earnings management. Peneliti selanjutnya diharapkan untuk mempertimbangkan variable tambahan yang lebih berpengaruh terhadap earnings management, memperpanjang periode pengamatan, serta menggunakan model pengukuran yang berbeda.